Визначення ризиків управління IT-проєктом з удосконалення МІС служби крові - Фіалка, К. А. (ХНУРЕ, 2025)
Blood services rely on Medical Information Systems (MIS) for managing processes like blood collection, processing, storage, and distribution, which directly impact medical assistance, reduce complications, and save lives. Continuous improvement of these systems is essential due to regulatory changes, international standards, technological advancements, and increasing demand for donor blood. This work defines key risks in managing ІТ projects in improvement MIS blood services and in MIS blood services, aiming to enhance system reliabilІТy, optimize operations, and support effective healthcare delivery.
Keywords: медицина; кров